Organic Cation Transporter I and Na+/taurocholate Co‐Transporting Polypeptide are Involved in Retrorsine‐ and Senecionine‐Induced Hepatotoxicity in HepaRG cells. Issue 2 (11th December 2021) - Enge, Anne‐Margarethe; Kaltner, Florian; Gottschalk, Christoph; Kin, Angelina; Kirstgen, Michael; Geyer, Joachim; These, Anja; Hammer, Helen; Pötz, Oliver; Braeuning, Albert; Hessel‐Pras, Stefanie
Abstract : Scope: 1, 2‐unsaturated pyrrolizidine alkaloids (PAs) are secondary plant metabolites that are found in many plant species throughout the world. They are of concern for risk assessment as consumption of contaminated foodstuff can cause severe liver damage. Of late, transporter‐mediated uptake and transport has advanced as a vital determinant of PA toxicity. In this study, the authors investigate a transporter‐mediated uptake of PAs and its implications in PA toxicity. Methods and Results: We show that transporter expression levels are significantly affected by treatment with the PAs senecionine (Sc) and retrorsine (Re) in the human hepatoma cell line HepaRG. Furthermore, the specific contribution to PA uptake of the two transporters Na + /taurocholate co‐transporting polypeptide (SLC10A1) and organic cation transporter I (SLC22A1), both belonging to the heterogeneous solute carrier super family, is investigated by means of a siRNA‐mediated knockdown approach. Knockdown of both uptake transporters result in reduced uptake of Re and Sc in a time‐dependent manner and attenuated PA‐mediated cytotoxic effects in HepaRG cells. Conclusion: Our results confirm previous findings of active transport mechanisms of PAs into hepatocytes and highlight the importance of toxicokinetic studies for the risk assessment of PAs. Abstract : 1, 2‐unsaturated pyrrolizidine alkaloids (PAs) can occur as food contaminants in products such as tea, honey, and spices. In the human hepatoma cell line HepaRG, PAs are suspected to be taken up by hepatic transporters such as SLC10A1 and SLC22A1. siRNA‐mediated knockdown of these two transporters significantly reduces the uptake and cytotoxicity of PAs.